Transformation of the zero valent iron dosage effect on anammox after long-term culture: From inhibition to promotion. (March 2019) - Guo, Beibei; Chen, Yuanhao; Lv, Lu; Ahmad, Hafiz Adeel; Ni, Shou-Qing; Ren, Liying; Cui, Zhaojie; Fang, Xu; Qiao, Zhuangming; Ding, Shaowu
Graphical abstract: Highlights: ZVI (1 g/L) first inhibited and then promoted anammox growth after long-term culture. High dosage ZVI shortened anammox start-up time from 96 to 87 days. ZVI created suitable environment for anammox bacteria proved by 15 N isotopic test. Anammox quantity increased by 44.5% and 54% at 100 and 1000 ppm ZVI after 120 days. Abstract: In this paper, three bio-reactors were designed to determine the effects of different zero-valent iron (ZVI) powder dosages on anammox. Initially, a high ZVI dosage inhibited the anammox process, while anammox adopted the habitat after long-term culture. The continuous experiment indicated that R2 (100 mg ZVI/L) had no notable effect on shortening the anammox start-up time, while R3 (1000 mg ZVI/L) reduced the start-up time from 96 to 87 days. The stable nitrogen isotope test suggested that the anammox activity of R3 was higher than that of R1 (without ZVI powder) during the stabilisation stage. The anammox growth rate increased by 20% in R3, which was verified by the real-time quantitative PCR results. In comparison to the control, the anammox quantity increased by approximately 44.5% and 54% at 100 and 1000 mg/L on day 120, respectively, which is likely due to lower dissolved oxygen and oxide-reduce potential created by the ZVI powder. The addition of ZVI may release iron ions, reduce the DO and ORP, and regulate the habitat pH conditions, which are beneficial for promoting anammox bacteria. Moreover, ZVI may directly partake in the anammox reaction pathway and improve the total nitrogen removal.